A Novel Light Weight and Automatic Authentication based on Centralized Approach for Pervasive Environment: A Novel Light Weight and Automatic Authentication Approach for Pervasive Environment - Khan, Muhammad Nawaz; Nazir, Muhammad (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Today is the age of hyper-connectivity, no standalone system ever exist. Now each device has the processing and communicating capabilities. Pervasive computing brings all these devices into a uniform layer for ease of use and for providing on fly services. In pervasive environments, smart devices communicate each other to provide pervasive services according to the user modes and contexts. To construct an ad hoc and un-structure network of heterogeneous entities and to standardize all different technologies into a uniform solution, many technical and functional challenges are need to be addressed. With dissimilar nature and distributed control over the resources in unfriendly situation the pervasive environments always in trouble due to lack of proper security system. For consistent dynamic flow of services in an ad hoc pervasive network, the authentication of users, devices, services and process are critical. Here in this research work we proposed “A novel light weight and automatic authentication scheme based on centralized approach for pervasive environment”. In this approach a central base station is responsible for providing resources and implementing security policy for all entities. Public Keys, Public key Certificates, Nonce, IDs and time stamps are parameters used in the proposed scheme. The new scheme is validated and analyzed in a simulator in the presence of attacker. The proposed model is designed to prevent most sophisticated DoS attacks and man in middle attacks.